ANALISIS NILAI TAMBAH KEDELAI SEBAGAI BAHAN BAKU TEMPE DI DESA ANGKATAN LOR, KECAMATAN TAMBAKROMO, KABUPATEN PATI - Wiwik Lestari; Djoko Sumarjono; Titik Ekowati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
Agroindustry is one of the important sub-sectors to be developed. The development of agroindustry is expected to be able to absorb agricultural products from farmers. Agricultural products that are still in the form of primary products will be processed into secondary or tertiary products so that they will produce added value. The added value of a product is very important to increase the selling price of the product. The purpose of study are (1) calculate and analyze the value of tempe from the processing process to the consumer's hand, (2) analyze the effect of the amount of soybeans, the price of tempeh and the contribution of other inputs to the added value of tempe. The method used in this study is the census method. Sampling is done by taking all respondents totaling 34 tempe producers through interviews with the help of questionnaires. The added value was analyzed using the Hayami method. Test the difference in tempe value-added ratio using one sample t test. The test of the effect of the amount of soybeans, the price of tempe and the contribution of other inputs to added value using Multiple Linear Regression. Based on the results of the study it can be seen that the added value obtained from the processing of soybeans into tempe is significantly classified as moderate, which is equal to 34.65%. The price of tempe and the contribution of other inputs have a significant effect on the amount of added value of tempe, while the amount of soybeans does not significantly influence. The amount of added value produced shows that the tempe business can be developed. In order to increase the added value of tempe, tempe producers are advised to reduce the contribution costs of other inputs, especially on fuel costs and increase the selling price of tempe.